1990
DOI: 10.3109/02713689009003477
|View full text |Cite
|
Sign up to set email alerts
|

The quantity of rhodopsin in human eyes

Abstract: The content of rhodopsin in the eyes of 15 donors (30 eyes) was determined. Both retinal and pigment epithelial fractions were collected from each globe, extracted using 1% CTAB, and the rhodopsin difference spectrum of each fraction was obtained separately. The total amount of rhodopsin, obtained by summing the amounts recovered from the retinal and PE fractions, ranged from 2.00 to 11.94 (median: 6.40) nmoles/eye. Previously reported mean values of about 3.5 to 4.0 nmoles per retina have been obtained using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 7 publications
2
48
0
1
Order By: Relevance
“…The caliber of the retinal arterioles adjusts to perturbations in blood oxygen levels ("autoregulation"). Logistic growth curve showing human rhodopsin content [40] as a function of age. The red arrow indicates the age of ROP onset in preterm infants [41].…”
Section: Discussionmentioning
confidence: 99%
“…The caliber of the retinal arterioles adjusts to perturbations in blood oxygen levels ("autoregulation"). Logistic growth curve showing human rhodopsin content [40] as a function of age. The red arrow indicates the age of ROP onset in preterm infants [41].…”
Section: Discussionmentioning
confidence: 99%
“…These are two important issues which need to be noted in terms of retinal architecture and retinal metabolism: (1) During the last 12 weeks of a normal pregnancy, the retina develops rapidly [25][26][27]. Therefore, there are significant differences between retinal properties in premature infants with different gestation ages.…”
Section: The Human Retina Is Immature During Rop Developmentmentioning
confidence: 99%
“…The reduction in photoreceptor function (PIII/a-wave amplitude) could be explained by a reduction in photoreceptor numbers, outer segment length, or the number of cGMP gated channels expressed within photoreceptor outer segments. 25 Previous studies have reported a reduction in outer segment length in the rat 67 and mouse 10 models of OIR, with no change in the number of photoreceptor nuclei. 11 Until recently, it was not clear why photoreceptors were affected in OIR, given that the disease was generally believed to specifically affect the intraretinal blood vessels, while the choroidal vasculature, which supplies the photoreceptors, 68,69 was largely believed to be intact.…”
Section: Rats With Oir Have Deficits In Both Rod and Cone Pathway Funmentioning
confidence: 99%